The practitioner's guide to the PCT - Erstling, Jay A. (ABA, American Bar Association, Intellectual Property Law Section, 2023)
"The objective of the revised edition of The Practitioner's Guide to the PCT is to continue the process of demystifying the PCT. The guide is based on the authors' many years of experience with the system, on the numerous PCT seminars and presentations they have given, and on the important lessons they have learned from the mistakes they have made"--
Keywords: Patent Co-operation Treaty / (1970 June 19); Patents (International law); Patent practice